Penguatan Peran Komunitas dalam Pengelolaan Sampah Berkelanjutan melalui Edukasi dan Inovasi Kreatif di Desa Senden: Strengthening the Role of the Community in Sustainable Waste Management through Education and Creative Innovation in Senden Village - Antriyandarti, Ernoiz; Ilham, Habib Muhammad; Savitri, Nurul; Maharani, Hilda; Mahmudah, Kavina Isyna; Putra, Ignatius Evan Andaru; Triyusopin, Heppy Dhemes; Al Fajri, Habiburrosyad; Dwijayanti, Jesica Gloria; Fauzi, Muhammad Alif; Rusamsi, Leonardo Putra (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Effective waste management remains a problem in Senden Village, especially regarding waste sorting. This issue encourages the KKN UNS 150 2024 team to conduct education related to waste management in the form of community service. The aim of this activity is to raise public awareness about the importance of effective and sustainable waste management and to encourage creative innovations in waste utilization. The method applied includes outreach and hands-on practice. The community service activities carried out include training on making candles from used cooking oil, the Merah Putih Environment Challenges, and socialization on the introduction of the 3Rs. The training on making candles from used cooking oil is aimed at the PKK mothers in Ngabean Hamlet. The result of this activity is the community's skill in processing used cooking oil waste into aromatherapy candles. The Merah Putih Environment Challenges activity targets a larger scope, specifically the mothers in Ngabean Hamlet. The outcome of this activity is the creation of handicrafts from inorganic waste. The socialization on the introduction of the 3Rs (reduce, reuse, recycle) is directed at the students of SD Negeri Senden 2. This activity effectively enhances students' understanding and awareness regarding proper waste management. The conclusion of this community service activity is that the residents of Senden Village, particularly those in Ngabean hamlet, are expected to have a good understanding of waste management and be prudent in handling it.